Synthesis of an Iron(IV) Aqua–Oxido Complex Using Ozone as an Oxidant. (10th April 2018) - Schaub, Stefan; Miska, Andreas; Becker, Jonathan; Zahn, Stefan; Mollenhauer, Doreen; Sakshath, Sadashivaiah; Schünemann, Volker; Schindler, Siegfried
Abstract: The iron(IV) oxido complex [(tmc)Fe=O(OTf)]OTf with the macrocyclic ligand 1, 4, 8, 11‐tetramethyl‐1, 4, 8, 11‐tetraazacyclo‐tetradecane (tmc) has been synthesized using ozone as an oxidant. By adding water to this compound the complex [(H2 O)(tmc)Fe=O)](OTf)2 could be prepared. This complex is important in regard to a better understanding of the reactivity of Fe IV oxido complexes. Mössbauer measurements using the solid compound showed an isomer shift of δ =0.19 mm s −1 and a quadrupole splitting Δ E Q =1.38 mm s −1, confirming the high‐valent Fe IV state. DFT calculations were performed and led to an assignment of triplet spin multiplicity. Crystallographic characterization of [(H2 O)(tmc)Fe=O)](OTf)2 as well as of starting materials [(tmc)Fe(CH3 CN)](OTf)2 and [(tmc)Fe(OTf)]OTf together with previous results strongly suggest that [(H2 O)(tmc)Fe=O)](OTf)2 was formed similar to the oxido–hydroxido tautomerism analogous to heme systems.